Poverty and food security impacts of sustainable intensification: Evidence from Ethiopia - Orkhan Sariyev; Jacob Asravor; Manfred Zeller (Food Security, 2025)
As sustainable intensification is a major pathway for improving agricultural productivity and reducing the environmental impacts of land use, the Government of Ethiopia and international development organizations have been promoting several practices and technologies for sustainable intensification. Using panel data from 368 farming households in Ethiopia from 2014, 2016, and 2019, this study gauges the poverty and food security impacts of Integrated Soil Fertility Management technologies and their combined use with conservation agriculture practices, specifically minimum tillage and crop rotation.~We find significant positive effects of ISFM adoption in terms of increasing dietary diversity and food expenditure and reducing food insecurity. In terms of poverty, ISFM adoption decreases the probability of being poor, the poverty gap, and the severity of poverty. When combined with CA practices, we find that the effects are consistently larger for farmers who integrate ISFM and CA for all food security and poverty measures. Our findings strongly suggest that the adoption of ISFM technologies has significant positive implications for poverty reduction and improved food security. These benefits are likely to gain a considerable boost if ISFM technologies are applied together with CA practices.
Keywords: 630; Technology adoption; Integrated soil fertility management; Conservation agriculture; Multinomial endogenous switching regression